RE-VICTORY OF THE SOCIALIST CANDIDATE IN THE CHILEAN PRESIDENTIAL ELECTION 2006 - Nur Laili (2009)
ABSTRACT The research discusses about Michelle Bachelet's victory as socialist candidate in Chilean presidential election 2005- 2006. The problem background begins from fluctuant patterns of Socialist candidates victories which were gained in 1970 through Salvador Allende, in 2000 through Ricardo Lagos Escobar, and the latest one in 2006 through Michelle Bachelet. In addition, it become more interesting to discuss in which Michelle Bachelet is an agnostic and a single- parent of her three chil